Pelvimetry by Reformatted Computed Tomography in 290 Female Pelvis: Morphometric Variations Regarding Age - Vázquez Barragán, Miguel Ángel; Garza Báez, Azalea; Morales Avalos, Rodolfo; Martínez González, Brenda; Jacobo Baca, Guillermo; Pinales Razo, Ricardo; Quiroga Garza, Alejandro; De la Fuente Villarreal, David; Elizondo Riojas, Guillermo; Elizondo Omaña, Rodrigo Enrique; Guzmán López, Santos (2016)
The Mexican government passed a new reform of article 11 of the General Law in 2014 regarding Women's Access to a Life Free of Violence, which states that a cesarean section may not be performed if a vaginal birth is viable. Cesarean sections are excessively indicated in Northen Mexico, using the diagnosis of cephalopelvic disproportion due to a narrow pelvis. Currently, there is no standardized morphometry of the female pelvis in a Mexican population to establish adequate diagnostic parameter. Our study measures the pelvic diameters of the birth canal using abdominopelvic computed tomography (CT). Two hundred and ninety CT from Mexican women between the ages of 18 and 50 were collected and 3D reformatted in order to morphologically measure the pelvic diameters of clinical relevance. Measurements were conducted by two diagnostic imaging specialists. The mean and standard deviation of the measured diameters were: anatomical conjugate diameter (ACD) 11.65±0.99 cm, the obstetric conjugate diameter (OCD) 11.73±0.98 cm, diagonal conjugate diameter (DCD) 12.49±0.98 cm and Interspinous distance (ISD) 10.41±0.78 cm. Significant differences were found in all four mean diameters in between the 20–29 age groups versus the >40, as well as between the 30–39 groups versus the >40. Our study shows that as Mexican women get older, the mean pelvic diameters become narrower.